2020
DOI: 10.18186/thermal.672297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Field Orientation on Nanofluid Free Convection in a Porous Cavity: A Heat Visualization Study

Abstract: Effect of magnetic field orientation on free convection of several water-based nanofluids in a square porous cavity is analyzed in this study. To this aim, the heatline visualization technique is implemented for the first time. Moreover, streamlines and isotherms are employed to present fluid flow and temperature distribution. The governing equations are transformed into a dimensionless form and then solved using the finite-volume method. Computations are undertaken for different orientations and magnitudes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Hence, more experiments are highly recommended to identify the operating conditions in which the PD is minimized, while the enhancement in HTC is maximized. (5) The formation of fouling on the heating surface over the 1000 minutes of experiments showed that the HTC of the NF may drop by 21.6% due to the thermal resistance induced by the fouling layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, more experiments are highly recommended to identify the operating conditions in which the PD is minimized, while the enhancement in HTC is maximized. (5) The formation of fouling on the heating surface over the 1000 minutes of experiments showed that the HTC of the NF may drop by 21.6% due to the thermal resistance induced by the fouling layer.…”
Section: Discussionmentioning
confidence: 99%
“…Boiling heat transfer and bubble formation are wonderful phenomena with lots of complex mechanisms and sub-phenomena, which are most of the time unknown and need further research [1,2]. Generally, boiling occurs on the boundary between the liquid and vapour on which the pressure of liquid equals to its saturation pressure and the temperature is the main external parameter which causes the boiling phenomenon to occur [1,[3][4][5][6]. The boiling mechanism is associated with the generation and movement of small bubbles which intensify the heat transfer between the liquid and vapour phases [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Ogut [8] introduced second law of thermodynamics to analyze mixed convection in an inclined liddriven cavity in presence of magnetic field and pointed out the fluid flow and entropy generation decrease for increase in Hartmann number. After that, the heatline visualization technique was first time implemented by Zahmatkesh and Ardekani [9] to investigate the effect of magnetic field orientation on free convection flow of nanofluids in a square porous cavity. Their results demonstrated the heat transfer rate deteriorates for the increase in magnetic field strength.…”
Section: Introductionmentioning
confidence: 99%
“…Manca et al [14] numerically studied mixed convection in a channel with an open cavity and their results showed that maximum temperature values decrease with the increase in Reynolds and Richardson numbers and the highest thermal performance in terms of both maximum temperature and average Nusselt number achieved in the opposing forced flow mode. Later on, Manca et al [15] experimentally investigated this analysis [9] and found that Nusselt numbers increase when the ratio of the length to the height of cavity increase for a considered range of Richardson numbers. Rahman et al [16] numerically studied the development of magnetic field effect on mixed convective flow in a horizontal channel.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently Bakar et al [24] studied the effect of magnetic field on fluid flow and heat transfer in a two-dimensional square cavity numerically. The streamlines and isotherm plots and the variation of Nusselt numbers on hot and cold walls were presented.Zahmatkesh and Ardekani [25] analyzed the effect of magnetic field orientation on free convection of several water-based nanofluids in a square porous cavity. Inspection of the results demonstrates that increase in the magnetic field strength deteriorates the heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%